Pengaruh Independensi Auditor, Kualitas Audit, Manajemen Laba, Dan Komisaris Independen Terhadap Integritas Laporan Keuangan (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar Di BEI Periode 2014-2017) - Ayem, Sri; Yuliana, Dewi (AKMENIKA, 2019)
The purpose of this study was to determine the effect of auditor independence, audit quality, earnings management, and independent commissioners on the integrity of financial statements. This research is included in descriptive research. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) during 2014-2017. The sample in this study was determined using a purposive sampling method and obtained 25 companies, samples in the 4 years of the annual financial report. The type of data used is secondary data. To find out the influence between independent variables and the dependent variable using the method of multiple regression analysis. The results of this study indicate that auditor independence has no significant effect, audit quality has no significant effect, earnings management has a significant effect, independent commissioners have a significant effect on the integrity of financial statements.